2003
DOI: 10.1111/j.1745-493x.2003.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interpersonal Satisfaction on Repurchase Decisions

Abstract: SUMMARY Having once made a purchase from a supplier, customer satisfaction has been found to drive buyers’decisions about the firms from which they will repurchase goods or services. Interpersonal satisfaction, the gratification that buyers receive from relationships with salespeople, is an important component of overall customer satisfaction. Even with the growing role of technology in procurement and supply chain management, interpersonal relationships between individual buyers and sellers are an important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Ramsey and Sohi (1997) show that satisfied customers are more likely to anticipate future interactions with their salespeople, and Ganesan (1994) suggests that the more satisfied buyers are, the more likely they are to adopt a long-term relational view. Other researchers have shown that customer satisfaction is a good predictor of buyer behavior; both Brady and Cronin (2001) and Preis (2003) demonstrate that satisfaction drives the intention to repurchase, and Johnson, Barksdale, and Boles (2003) report that it makes customers more willing to pass leads on to salespeople. Similarly, satisfied customers are more likely to recommend their salespeople and spread good word of mouth about them (Brady & Cronin, 2001).…”
Section: Relationship Qualitymentioning
confidence: 96%
“…Ramsey and Sohi (1997) show that satisfied customers are more likely to anticipate future interactions with their salespeople, and Ganesan (1994) suggests that the more satisfied buyers are, the more likely they are to adopt a long-term relational view. Other researchers have shown that customer satisfaction is a good predictor of buyer behavior; both Brady and Cronin (2001) and Preis (2003) demonstrate that satisfaction drives the intention to repurchase, and Johnson, Barksdale, and Boles (2003) report that it makes customers more willing to pass leads on to salespeople. Similarly, satisfied customers are more likely to recommend their salespeople and spread good word of mouth about them (Brady & Cronin, 2001).…”
Section: Relationship Qualitymentioning
confidence: 96%
“…Arieti (1974) and Fromme and O'Brien (1982) consider satisfaction as an emotion, whilst other researchers have stated that satisfaction is an expressed emotional reaction to a service context (Russell, 1980;Havlena and Holbrook, 1986). Preis (2003) suggests that the relationship between a service provider and the consumer has a positive impact on whether repurchase will occur. Therefore, personality as the antecedent influence of the interactions between consumersand-service providers may affect both the level of consumer satisfaction evaluation and the intention to repurchase.…”
Section: Background To Personality and Emotions Researchmentioning
confidence: 96%
“…12, No. 4; respectful interactional relationship reflected by the way customer are being treated and dealt with, and from other side would highlight the need from mobile companies to be transparent and clear of the information they exchange with the customer, as interactional relationship proven to impact the trust relationship directly as highlighted by (Preis, 2003) that the gratification buyers receive from relationships with sales people, is an important component of overall customer satisfaction, whereby gratification are indicated as interpersonal satisfaction.…”
Section: Discussionmentioning
confidence: 99%